2018
DOI: 10.1186/s12864-018-5221-9
|View full text |Cite
|
Sign up to set email alerts
|

Combining multiple functional annotation tools increases coverage of metabolic annotation

Abstract: BackgroundGenome-scale metabolic modeling is a cornerstone of systems biology analysis of microbial organisms and communities, yet these genome-scale modeling efforts are invariably based on incomplete functional annotations. Annotated genomes typically contain 30–50% of genes without functional annotation, severely limiting our knowledge of the “parts lists” that the organisms have at their disposal. These incomplete annotations may be sufficient to derive a model of a core set of well-studied metabolic pathw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 44 publications
1
28
0
Order By: Relevance
“…In this study, we sought to assess the impact of selected annotation pipelines on draft metabolic network reconstructions and downstream analyses of metabolic complementarity. Our results highlight significant differences between the output of the five tested standard pipelines at all examined levels, from the prediction of coding sequences to the selection of microbial communities, especially for EC annotations and hypothetical proteins, with levels of variability similar to those previously reported by Griesemer et al (2018) . Overall, the number of reactions predicted in the final network mirrored the number of EC numbers predicted, with Prokka and IMG yielding both the highest number of EC annotations and reactions.…”
Section: Discussionsupporting
confidence: 61%
“…In this study, we sought to assess the impact of selected annotation pipelines on draft metabolic network reconstructions and downstream analyses of metabolic complementarity. Our results highlight significant differences between the output of the five tested standard pipelines at all examined levels, from the prediction of coding sequences to the selection of microbial communities, especially for EC annotations and hypothetical proteins, with levels of variability similar to those previously reported by Griesemer et al (2018) . Overall, the number of reactions predicted in the final network mirrored the number of EC numbers predicted, with Prokka and IMG yielding both the highest number of EC annotations and reactions.…”
Section: Discussionsupporting
confidence: 61%
“…No single approach is a panacea. Rather, it has been demonstrated numerous times that optimal results in bioinformatics are obtained by combining many different approaches and data sources together to obtain a consensus result ( 71 ). One of the biggest impediments to building such a consensus approach for biology today is the lack of a single standard ontology for describing gene functions.…”
Section: Discussionmentioning
confidence: 99%
“…Diverse evolutionary groups have evolved specific sets of metabolic reactions to obtain their required energy and biomass. On average, more than 50% of the genes in microbial genomes code for metabolic functions (Griesemer et al, 2018) and metabolic genes are often found to be horizontally transferred (Goyal, 2018). The different sets of metabolic reactions used in different contexts by microbes reflect patterns and mechanisms of their genome evolution.…”
Section: Discussionmentioning
confidence: 99%